16 Investigating the effects of under-triage by existing major incident triage tools. Issue 12 (23rd November 2017) - Vassallo, James; Smith, Jason
Abstract : Introduction: Triage, the process of prioritising patients on the basis of clinical acuity, is a key principle in the effective management of a major incident. The overall effectiveness of the triage process is not only a balance between identifying those who need or don't need a life-saving intervention, but also those who are under or over-triaged as either incorrectly needing/not needing intervention. The primary aim of this study was to describe the implications of under-triage using existing major incident triage tools, including the 2013 National Ambulance Resilience Unit (NARU) Sieve. The secondary aim was to describe the safety profile of the Modified Physiological Triage Tool (MPTT) in comparison to other triage tools, and to report mortality and identification of serious injury (AIS>3) in discrete AIS body regions. Methods: A retrospective database review was undertaken using the UK Trauma Audit Research Network for all adult patients (> 18 years) between 2006–2014. Patients were defined as Priority One using a previously published list. Using first recorded hospital physiology, patients were categorised by the MPTT, NARU Sieve and existing Triage Sieve. Data are presented as number (%) and median (IQR) as appropriate. Categorical data were analysed using a Chi Square test and continuous data with a Mann-Whitney U test. Results: During the study period, 2 18 985 adult patients were included with 24 791 (19.5%) identified as Priority One. 70% were male, aged 51 years [33–71], ISS 16 [9–25] with road traffic collision the most common mechanism (34%). The MPTT demonstrated the lowest rate of under-triage (42.4%, p<0.001). Overall 30 day mortality for the Priority One cohort was 12.4%. Compared to existing methods, the MPTT under-triage population had significantly lower mortality (5.7%, p<0.001), identical to the overall study population. Patients under-triaged by the MPTT had significantly lower requirement for intubation, thoracocentesis and massive transfusion than both the NARU Sieve and Triage Sieve (p<0.001). Serious injuries to the thorax (47.0%) and head (27.4%) predominated, with the MPTT again significantly under-triaging fewer of these patients (p<0.001). Conclusion: This study has defined the effects of and compared the implications of under-triage when different triage tools are used in the context of a major trauma population. The MPTT misses fewer severely injured patients, with fewer LSIs necessary in the under-triaged population. We suggest that the MPTT should be considered as an alternative to existing major incident triage tools.